2019
DOI: 10.1093/nop/npz010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and added value of qualitative radiological review of 1H-magnetic resonance spectroscopy in evaluation of childhood brain tumors

Abstract: Background 1H-magnetic resonance spectroscopy (MRS) facilitates noninvasive diagnosis of pediatric brain tumors by providing metabolite profiles. Prospective studies of diagnostic accuracy and comparisons with conventional MRI are lacking. We aimed to evaluate diagnostic accuracy of MRS for childhood brain tumors and determine added clinical value compared with conventional MRI. Methods Children presenting to a tertiary pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Simply viewing MRS processed by the MR scanner software increased the radiologists' diagnostic accuracy and certainty of the correct diagnosis when added to conventional imaging. This reflects other paediatric studies in which adding MRS to conventional MRI significantly improved radiologists' diagnostic accuracy of brain tumours 23,24 and indicates that MRS can be a useful adjunct to MRI without sophisticated decision support software. The DSS gave both a comparison of the MRS with mean MRS from the three types of tumour and the results of a pattern recognition-based classifier.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Simply viewing MRS processed by the MR scanner software increased the radiologists' diagnostic accuracy and certainty of the correct diagnosis when added to conventional imaging. This reflects other paediatric studies in which adding MRS to conventional MRI significantly improved radiologists' diagnostic accuracy of brain tumours 23,24 and indicates that MRS can be a useful adjunct to MRI without sophisticated decision support software. The DSS gave both a comparison of the MRS with mean MRS from the three types of tumour and the results of a pattern recognition-based classifier.…”
Section: Discussionsupporting
confidence: 76%
“…Studies adding visual interpretation of MRS profiles to conventional MRI have been found to significantly improve radiologists' diagnostic accuracy of paediatric brain tumours. [23][24][25] Interpretation of MRS in addition to MRI, by a radiologist, was found to provide clinical benefit in selective cases. There is also some evidence that qualitative interpretation of MRS improves the accuracy of noninvasive diagnosis in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used PRESS localisation suffers from chemical shift artefacts, which become more apparent at higher field strength, and a recent consensus document has advised moving to a semiLASER localisation sequence [43]. MRS data is best analysed quantitatively using software methods which can fit the spectra to obtain metabolite concentrations, but it has also been shown that visual interpretation aids diagnostic accuracy when added to conventional MRI [44]. Spectroscopic imaging may be more appropriate than single-voxel spectroscopy for large diffuse tumours and may aid the identification of most aggressive regions, but implementation of the technique requires experience and is not part of the routine protocol [45].…”
Section: Multi-modal Advanced Mrimentioning
confidence: 99%
“…As a point of reference, earlier studies have documented human accuracy of pediatric brain tumor classification as approximately between 70% and 80% by pediatric neuroradiologists with Certificates of Added Qualification. 35,36…”
Section: Discussionmentioning
confidence: 99%